Analysis of Artificial Intelligence Algorithms for Enhancing Digital Marketing Efficiency - Arman Andrian; andri catur trissetianto andri; Ridwan (SYSTEMIC RESEARCH: Systemic and Information Technology Journal, 2025)
This research investigates the role of artificial intelligence (AI) algorithms in enhancing the efficiency of digital marketing efforts. Despite the rapid adoption of AI technologies in marketing, a significant research gap exists in understanding how these algorithms influence both performance metrics and user acceptance, while addressing implementation challenges and ethical concerns. The study aims to analyze the impact of AI algorithms on key digital marketing outcomes and explore the associated factors affecting their adoption. Employing a mixed-methods approach, quantitative data were analyzed using statistical models to measure performance improvements, while qualitative data were coded to extract themes related to benefits, challenges, and ethics. The results reveal that AI algorithms substantially improve conversion rates and click-through rates, with positive associations to perceived benefits and user acceptance. However, implementation barriers and ethical issues pose notable constraints on effectiveness. The novelty of this research lies in its integrated analysis combining quantitative metrics with qualitative insights, providing a holistic understanding of AI’s dual impact in marketing environments. The study concludes that while AI significantly advances digital marketing efficiency, careful consideration of practical and ethical dimensions is crucial for sustainable adoption.